Train excursion (Norfolk and Western) to West Jefferson, 1957. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 7-14-57 p.10C.
Train excursion (Norfolk and Western) to West Jefferson, 1957.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth